2020
DOI: 10.1002/pds.4989
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing drug utilization research in the Latin American region

Abstract: This is the first manuscript, and it is related to the challenges identified in the DUR area in the LatAm region. Drug utilization researchers in LatAm voluntarily participated in multiple discussions contributed with local data and reviewed successive drafts and the final document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 93 publications
(151 reference statements)
0
21
0
1
Order By: Relevance
“…En los últimos años, se han señalado las limitaciones para realizar EUM en los países de América Latina, incluyendo factores como la fragmentación de los sistemas de salud, la falta de bases de datos a nivel nacional y el escaso conocimiento de los decisores sobre este tipo de estudios (35) . Las comparaciones entre países de América Latina están pobremente documentadas y su validez está amenazada por el riesgo potencial de sesgo de extrapolación, considerando la disponibilidad de datos sobre el uso de medicamentos en el sector público (8) .…”
Section: Discussionunclassified
“…En los últimos años, se han señalado las limitaciones para realizar EUM en los países de América Latina, incluyendo factores como la fragmentación de los sistemas de salud, la falta de bases de datos a nivel nacional y el escaso conocimiento de los decisores sobre este tipo de estudios (35) . Las comparaciones entre países de América Latina están pobremente documentadas y su validez está amenazada por el riesgo potencial de sesgo de extrapolación, considerando la disponibilidad de datos sobre el uso de medicamentos en el sector público (8) .…”
Section: Discussionunclassified
“…Despite the aforementioned worldwide increased usage and application of RWD and RWE, in the South American context this information has generally only been utilized in academic research and pharmacovigilance [ 1 ]. For example, drug utilization research in Latin American countries has limitations due to fragmented healthcare systems, the lack of nationwide databases, or the poor knowledge of decision makers regarding these kinds of studies [ 8 ]. However, RWE usage could have an impact on the healthcare of the population in daily clinical practice as its visibility and practicality in the region increases.…”
Section: Real-world Data and Real-world Evidencementioning
confidence: 99%
“…58 Latin America is a region with a low literacy rate that affects directly the drug utilization research (DUR), which encompasses the use, efficacy, and safety of medicines based on local research. 59 This is primarily caused by the existence of a very limited generation of scientific publications by local investigators. 59 , 60 On the available studies, data collection bias has been identified since they present methodological issues such as limited validation, small sample size, and unavailability of information and involvement of the public sector.…”
Section: Introductionmentioning
confidence: 99%
“… 59 This is primarily caused by the existence of a very limited generation of scientific publications by local investigators. 59 , 60 On the available studies, data collection bias has been identified since they present methodological issues such as limited validation, small sample size, and unavailability of information and involvement of the public sector. 60 All this causes a significant impact in the clinical and regulatory decisions that impact directly the public health decision making.…”
Section: Introductionmentioning
confidence: 99%